Bridging the gap between ICAO level 4 and 5 in Aviation English: expectations and results - Gabrielė Masiulionienė; Gytė Tupčiauskaitė (Aviation, 2023)
The Authors investigated the Aviation English proficiency levels of Vilnius Tech Aircraft Piloting and Air Traffic Control (ATC) students by considering general English examination scores, marks for Aviation English modules and proficiency levels of a specialised speaking task. The aim was to assess how well students acquire the skills and abilities not only to pass an Aviation English proficiency examination (level 4), but also to obtain a higher level 5 necessary for a longer endorsement of their language certificate. Finally, it was determined which areas of language are the easiest and most difficult to master with regards to either a level 4 or 5 according to the ICAO (International Civil Aviation Organisation) Rating scale. It was found that four out of five students have the background skills to reach at least an ICAO level 4 upon graduating, however only a fifth are able to achieve a higher level 5. The proportion of level 5 students does not match the proportion of students with good initial general English results, so there should be a greater focus on improving the language training programme by making it more challenging and broadening its scope in terms of vocabulary and grammar in particular.